ASPEK HUKUM HUMANITER DALAM KRISIS KEMANUSIAAN TERHADAP ANAK DI KOLOMBIA TAHUN 2012-2015 - Maulana, Tengku Rafly; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes humanitarian law aspects in human crisis toward child in Colombia in 2012-2015. Colombia are state in Latin America region. Since 1964, Government of Colombia have crisis withe the separatism grouo that name a Fuerzas Armadas Revolucionarias de Colombia (Revolutionary Armed Forces of Colombia or FARC). FARC has recruted a child as sholdier and this action are not agreed with the humanitarian international law.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the humanitarian law aspects in human crisis toward child in Colombia. The theories applied in this research are realism perspective with the humanitarian law concept.The result about humanitarian law aspects in human crisis toward child in Colombia shows that crisis in Colombia are humanitarian crisis and children in Colombia has a recrut to be a child shouldier. humanitarian law aspects in human crisis toward child in Colombia based on source of law in humanitarian law likes Geneva Convention, Denhag Convention and Additional Protocoll. Supremacy of humanitarian laws in Colombias crisis are use transitional justice, diplomacy of getting to the table, roles of ICRC and coordination by National Colombia in toward a humanitarian crisis in Colombia.Key words: humanitarian laws, aspect, crisis and humanity